Radon (IntechOpen, 2023)
In the book Radon, some segments of modern research from a wide range of issues related to radioactive gas radon are presented. The purpose of this book is to emphasize the importance of the existence of the radioactive gas radon in the environment and to make this natural phenomenon a top issue because radon is included in class A human carcinogenesis. The chapters of the book show physical and chemical properties of radon and radon progeny; concentration, emanation, and transport of radon in ambient environments; detection of radon and radon progeny in different environments; passive and active radon measurement techniques; and calibration of a dosimeter for the detection of radon. This book will be of great importance to scientists from a wide range of research area on the phenomenon of radon and will be useful to those who are beginners in this area as well. Due to the impact of radon gas on health, the content of this book will be interesting to a wider audience.